Context and time based riskiness assessment for decision making - Hussain, Omar; Chang, Elizabeth; Hussain, Farookh; Dillon, Tharam S.; Soh, B. (IEEE Computer Society Press, 2006)
In an e-commerce interaction carried out in a Peer-to-Peer environment it is rational for the trusting peer to analyze the Risk that could be involved in dealing with a trusted peer as there is a lack of central management in these type of interactions. Risk analysis can be done by assimilating recommendations from other peers if there is no previous interaction history between the trusting peer and the trusted peer. But the assimilated recommendations might be according to the criteria of the recommending peer with the trusted peer, and it is not necessary for the trusting peer to have the same criteria in its interaction with the trusted peer as that of the recommending peer even thought it is interacting in the same context. Further it might interact in a different time as that of the recommending peer. The Risk that was present in a particular context and at a particular time might not be the same at a different time. Hence in this paper we discuss the process of the trusting peer assimilating the recommendations from the recommending peers according to the context, criteria and time of its interaction in order to determine the Riskiness value of the trusted peer, which would help it considerably in decision making.